Factors influencing self-management of Diabetes Mellitus; a review article - Kisokanth, G.; Prathapan, S.; Indrakumar, J.; Joseph, J. (My University, 2013)
To review recent data to identify the factors influencing the effective self-management of Diabetes Mellitus (DM). A review of the published literature on self-management of diabetes was performed. This involved searching databases using the search terms Self-management of Diabetes Mellitus, DM and its management, management of type 2 DM, prevalence of diabetes and risk factors for DM. Included studies were conducted in different parts of the world between 1993 and 2013. An attempt was made to contact corresponding authors for further information for this study. We included 34 articles in our review. Self-management of diabetes were consistent with those found in several studies, i.e. individuals most regularly followed their prescribed medication regimen and least regularly followed recommendation for lifestyle changes of diet and exercise. The important determinants of selfmanagement are transient situational factors such as environmental factors, psychological factors and social factors. Interventions to promote better self-management have reported in several studies. Initial improvement in better glucose control can be achieved by self-management education. Successful self-management of DM requires that individuals with DM frequently monitor their blood glucose levels and take required action in order to keep blood sugar within a physiological level. This can be achieved by self-management education, self-monitoring and social support. Cultural influences also have interfered with successful diabetes self-management. The chronic care model is recommended for the self-management of DM.
Keywords: Self-management; diabetes mellitus; self-education